2013
DOI: 10.1007/s11606-013-2357-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Victimization, Health Status, and VA Healthcare Utilization Among Lesbian and Bisexual OEF/OIF Veterans

Abstract: BackgroundMany lesbian and bisexual (LB) women veterans may have been targets of victimization in the military based on their gender and presumed sexual orientation, and yet little is known regarding the health or mental health of LB veterans, nor the degree to which they feel comfortable receiving care in the VA.ObjectiveThe purpose of this study was to examine the prevalence of mental health and gender-specific conditions, VA healthcare satisfaction and trauma exposure among LB veterans receiving VA care com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 13 publications
2
53
1
Order By: Relevance
“…There is a substantial and growing literature examining the impact of sexual orientation on mental health indicators among veterans, with an emphasis on the experiences of young female veterans [7-9]. This research shows that sexual minority veterans are more likely to experience military and childhood trauma, report less social and emotional support, and report worse mental health than heterosexual veterans.…”
mentioning
confidence: 99%
“…There is a substantial and growing literature examining the impact of sexual orientation on mental health indicators among veterans, with an emphasis on the experiences of young female veterans [7-9]. This research shows that sexual minority veterans are more likely to experience military and childhood trauma, report less social and emotional support, and report worse mental health than heterosexual veterans.…”
mentioning
confidence: 99%
“…For example, sexual minority status (determined either by self-identity or sexual behavior) was associated with higher odds of binge drinking among a general population of women (Lindley et al, 2012). Among veterans, a handful of studies have also demonstrated greater rates of substance use among lesbian and bisexual veterans compared to their heterosexual counterparts (Booth et al, 2011;Cochran et al, 2013;Mattocks et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing sexual minority and heterosexual women veterans, those who reported having had any sexual partnerships with women were more likely than those who reported only having had sexual partnerships with men to meet criteria for a lifetime substance use disorder, although alcohol misuse was not specifically examined (Booth, Mengeling, Torner, & Sadler, 2011). While two previous studies identified higher prevalence rates of alcohol misuse among sexual minority veterans compared to heterosexual veterans, both studies used only dichotomous measures of alcohol misuse (Cochran, Balsam, Flentje, Malte, & Simpson, 2013;Mattocks et al, 2013). Moreover, no previous study has assessed associations between sexual minority status and alcohol misuse severity among women veterans across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Lehavot and Simpson provide their perspective on how this important topic can be better examined in research studies 16. Mattocks et al conducted a cross-sectional study of OEF and OIF women Veterans at two VA facilities, asking also about sexual preference 17. LB women reported more sexual victimization both within the military and as children compared to heterosexual women.…”
Section: Reproductive Healthmentioning
confidence: 99%